The origins of the Scottish Reformation - Ryrie, Alec (Politics, culture, and society in early modern Britain., 2006)
The Scottish Reformation of 1560 is one of the most controversial events in Scottish history, and a turning point in the history of Britain and Europe. Yet its origins remain mysterious, buried under competing Catholic and Protestant versions of the story. Drawing on fresh research and recent scholarship, this book provides the first full narrative of the question. Focusing on the period 1525-60, in particular the childhood of Mary, Queen of Scots, it argues that the Scottish Reformation was neither inevitable nor predictable. A range of different?Reformations? were on offer in the sixteenth c.